Mucocutaneous manifestations in patients with rheumatoid arthritis: A cross-sectional study from Eastern India - Sudip Kumar Ghosh; Debabrata Bandyopadhyay; Surajit Kumar Biswas; Ivoreen Darung (Wolters Kluwer Medknow Publications, 2017)
Background: Cutaneous manifestations are fairly common in rheumatoid arthritis (RA) and they can help in early diagnosis, prompt treatment, and hence reduced morbidity from the disease. Aims: The objective of the present study was to find out the different patterns of dermatoses in a group of patients with RA from Eastern India. Methodology: Consecutive patients fulfilling the American Rheumatism Association 1987 revised criteria for the classification of RA and who had different dermatoses were included in this cross-sectional study done over a period of 8 years in a tertiary care hospital in Eastern India. Thorough clinical examination and appropriate laboratory investigations were performed as needed. Data were recorded in a predesigned schedule, and appropriate statistical analysis was done. Results: We studied 111 evaluable patients with an age range of 19-71 years and a female to male ratio of 7:1. The mean disease duration of RA was 6.5 years. Cutaneous infections as a group was the most common mucocutaneous manifestation (34.2%) followed by xerosis including ichthyotic skin changes (27%), pigmented purpuric dermatoses (14.4%), leg ulcer (9.9%), periungual telangiectasia (9.9%), rheumatoid nodules (RNs) (8.1%), purpura and ecchymoses (7.2%), small vessel vasculitis in (7.2%), corn and callosities (6.3%), palmar erythema (4.5%), and neutrophilic dermatosis (4.5%). Raynaud's phenomenon was found in 3.6% patients and panniculitis in (3.6%) patients. Rheumatoid factor (RF) and anti-cyclic citrullinated peptides antibody were positive in 74.8% and 88.3% patients, respectively. No statistically significant difference of incidence of leg ulcer, small vessel vasculitis, RN, or Raynaud's phenomenon could be noted between RF positive and negative groups. Limitations: Being an institution-based study, the study findings may not reflect the true situation in the community which remained a limitation of this study. Conclusion: While some of the features of this study were analogous to Western data, other features showed discordance which may be due to ethnic variations among the patients with RA.